2018
DOI: 10.3389/fphys.2018.01719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Eight-Week Superimposed Submaximal Dynamic Whole-Body Electromyostimulation Training on Strength and Power Parameters of the Leg Muscles: A Randomized Controlled Intervention Study

Abstract: The purpose of this study was to assess the effects of dynamic superimposed submaximal whole-body electromyostimulation (WB-EMS) training on maximal strength and power parameters of the leg muscles compared with a similar dynamic training without WB-EMS. Eighteen male sport students were randomly assigned either to a WB-EMS intervention (INT; n = 9; age: 28.8 (SD: 3.0) years; body mass: 80.2 (6.6) kg; strength training experience: 4.6 (2.8) years) or a traditional strength training group (CON; n = 9; age: 22.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 37 publications
3
62
0
Order By: Relevance
“…These results are in agreement with those reported by Kemmler et al [14] and Micke et al [7], confirming the possible alternative or contributive use of the WB-EMS methods to the efficient training of strength and power. In particular, with respect to the study by Micke et al (2018), which focused on the strength and power parameters of the leg muscles, our study added new findings investigating the effects of WB-EMS programs on strength and power parameters of upper and lower limbs using force-velocity curves as suggested by Bosco and Komi [20], Bosco [21], and Zatsiorsky and Kraemer [22]. In particular, ▶ Figs 2-5 indicate the right shift of the entire curves, after the three treatments, demonstrating that both the area of force and that of velocity have increased in a similar way, thus causing harmonics adaptations in all the expressions of muscular force we considered [23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with those reported by Kemmler et al [14] and Micke et al [7], confirming the possible alternative or contributive use of the WB-EMS methods to the efficient training of strength and power. In particular, with respect to the study by Micke et al (2018), which focused on the strength and power parameters of the leg muscles, our study added new findings investigating the effects of WB-EMS programs on strength and power parameters of upper and lower limbs using force-velocity curves as suggested by Bosco and Komi [20], Bosco [21], and Zatsiorsky and Kraemer [22]. In particular, ▶ Figs 2-5 indicate the right shift of the entire curves, after the three treatments, demonstrating that both the area of force and that of velocity have increased in a similar way, thus causing harmonics adaptations in all the expressions of muscular force we considered [23].…”
Section: Discussionsupporting
confidence: 93%
“…Electrical muscle stimulation (EMS) consists of local application of an electric current to elicit a muscle contraction [1]; in sports training, the most commonly used technique is percutaneous electrical stimulation, where the electrostimulation is applied to the muscular belly [2]. Several studies performed both in the medical and sports fields have extensively analyzed the principles and the parameters of the EMS [mainly considering the intensity of the electrical stimulus (Amp), the frequency (Hz), and the width of the impulse] and the physiological adaptations to the EMS training [3][4][5][6][7][8][9][10][11][12]27]. Certainly, fewer studies have taken into account whole-body electromyostimulation (WB-EMS), a training method associated with a voluntary pre-contraction both isometric or dynamic [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wirtz et al [72] found improvements in the leg flexors in an isoinertial power test with a leg curl machine. The same happened in the leg curl power strength in Wirtz et al [85]. Their studies were carried out with young trained males, but they agreed with the results of the present study in the successfulness of the WB-EMS enhancing the power in an isolated way.…”
Section: Power and Velocitysupporting
confidence: 92%
“…Other studies designed interventions whose control group carried out exercises of the same nature as the experimental group, but their training did not match the volume and frequency of training loads (58,60,114,115). The protocol of the present study intends to carry out an experimental phase in which the interventions of both groups are completely comparable in terms of type of movements and training volume (116)(117)(118). It will allow identifying precisely the isolated effect of the WB-EMS.…”
Section: Discussionmentioning
confidence: 99%